2018
DOI: 10.1111/ggi.13514
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for achieving oral intake in older patients with aspiration pneumonia: Videofluoroscopic evaluation of swallowing function

Abstract: Aspiration on videofluoroscopy, swallowing status before admission, nutritional status and duration of non-oral intake are important factors for acquiring oral intake. These results might be helpful for the management of older patients with aspiration pneumonia. Geriatr Gerontol Int 2018; 18: 1469-1473.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Therefore, our study differs from the previous study in terms of the causative disease of the patients and the timing of the evaluation of the swallowing function. Previous studies limited to aspiration pneumonia have conducted research using big data 4 and VF findings 5 ; however, none of these reports indicated whether their survey items with significant differences were suitable screening tests to predict the prognosis of oral intake status for patients with aspiration pneumonia. Our study is therefore the first to suggest that the Hyodo‐Komagane score may be useful as a screening test for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, our study differs from the previous study in terms of the causative disease of the patients and the timing of the evaluation of the swallowing function. Previous studies limited to aspiration pneumonia have conducted research using big data 4 and VF findings 5 ; however, none of these reports indicated whether their survey items with significant differences were suitable screening tests to predict the prognosis of oral intake status for patients with aspiration pneumonia. Our study is therefore the first to suggest that the Hyodo‐Komagane score may be useful as a screening test for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study using videofluorography (VF) suggested that the penetration-aspiration scale (P-A scale) is useful for predicting whether or not nutrition can be completely taken orally after 4 weeks of VF, indicating the importance of conducting VF and performing nutritional management at an early stage of hospitalisation. 5 However, VF requires large-scale equipment, and it cannot be performed multiple times over a short period because of concerns about the exposure dose. However, videoendoscopic examination of swallowing (VE) requires only relatively simple equipment, and it can be performed multiple times regardless of location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on age, sex, underlying disease (cerebrovascular, gastrointestinal, respiratory, circulatory, orthopedic, and other), past medical history, and comorbidities (head and neck tumors, gastroesophageal surgery, cerebrovascular disease, chronic lower respiratory airway disease, diabetes mellitus, and dementia), body mass index (BMI), frequency of use of urinary catheters, frequency of use of proton pump inhibitors and angiotensin-converting enzyme inhibitors, length of hospital stay, time from hospitalization to resuming oral intake, mortality, and swallowing ability (positive dysphagia screening rate, MSS, PAS, and FOIS scores at discharge) were collected from the medical records or from video recordings after referencing earlier studies of factors that may affect oral intake [ 25 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…36 In non-ventilated patients, the microbiome and the environment is more fluid and subject to dilution effects of saliva, which might negatively impact efficacy. 37,38 It is also possible that the time to onset which defines NVAP reduces the potential prophylactic Heterogeneity: I 2 = 74%, tau 2 = 0.1921, p = 0.05 Table 6 Forest plot of the non-RCTs (enhanced oral care in the prevention of NVAP). Review: enhanced oral hygiene maintenance for the prevention of non-ventilated pneumonia.…”
Section: Other Studiesmentioning
confidence: 99%